Gender Equality Norms in Regional Governance : Transnational Dynamics in Europe, South America and Southern Africa - Vleuten, Anna van der; Eerdewijk, Anouka van; Roggeband, Conny; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
This book analyses the diffusion of norms concerning gender-based violence and gender mainstreaming of aid and trade between the EU, South America and Southern Africa. Norm diffusion is conceptualized as a truly multidirectional and polycentric process, shaped by regional governance and resulting in new geometries of transnational activism.
Keywords: Science; Science, general